HARMONY OF FREEDOM AND RESPONSIBILITY IN MODERN SOCIETY (Conferencea, 2024)
The crisis of the social system and the new processes of development of modern society require the development of a new worldview on this issue. If we talk about the specifics of understanding freedom and responsibility of a modern person, it should be emphasized that the world is entering a period of a civilizational turning point, when many traditional ways of being a person need to be changed.